hMSC production in disposable bioreactors with regards to GMP and PAT - Cierpka, Katharina; Elseberg, Christiane L.; Niss, Knut; Kassem, Moustapha; Salzig, Denise; Czermak, Peter (My University, 2013)
Reactor concepts for human mesenchymal stem cell (hMSC) production are introduced. Thereby, special interest is laid on the realization of these concepts as disposables fulfilling the GMP and PAT requirements. The specialty of the hMSC production process is the cell itself being the product. This results in completely different process requirements compared to e.g. protein production in mammalian cells. Thus, great attention has to be given to the shear sensitivity of the cells. The cultivation and the harvest of the cells have to be very gentle to neither influence cell viability nor cell differentiability. Further, the production process should not cause any undesirable cell changes. For hMSC production, cell harvest is the main challenging process step. The reactor concepts should be suitable for hMSC production for clinical trials as ATMPs. Therefore, disposable systems are especially applicable. The review describes more detailed bone marrow-derived hMSC production in a disposable stirred tank reactor as promising reactor concept.
Keywords: Disposable reactor; Fixed-bed reactor; hMSC; Stem cell production; Stirred-tank reactor